A high-permeability anti-cracking coal rock mass reinforcing polyurethane composite material and a preparation method thereof
Patent Information
- Application Number
- CN202611360991.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-03
- Publication Date
- 2026-10-16
AI Technical Summary
[0006]为了克服上述背景技术中现有聚氨酯煤岩体加固材料渗透能力不足、固化后易脆裂以及界面稳定性较差的难题,本发明的目的在于提供一种高渗透抗开裂煤岩体加固聚氨酯复合材料及其制备方法,采用儿茶酚-硅氧协同改性物对聚氨酯体系进行界面增强,并引入邻苯二甲酸二甲酯作为渗透调控有机小分子,从而构建具有柔性缓冲与深部渗透能力的复合加固体系,进而提高材料对煤岩体微细裂隙的渗透加固能力以及长期抗开裂稳定性;本发明能够有效提高煤岩体加固后的结构稳定性与服役安全性
[0025] This invention employs a catechol-siloxane synergistic modifier to synergistically enhance a polyurethane system. The ortho-phenolic hydroxyl groups in catechol can form multi-point interfacial interactions with the hydrolyzed silanol structure, working in conjunction with the siloxane network structure formed by tetraethyl orthosilicate. This constructs a flexible-rigid synergistic interfacial layer during polyurethane curing, effectively alleviating localized stress concentration caused by curing shrinkage and improving the material's crack resistance and long-term structural stability. Furthermore, this synergistic modification method features a simple reaction pathway and well-defined structure, demonstrating both good inventiveness and full disclosure. In addition, this invention introduces dimethyl phthalate as a permeation-regulating organic molecule, effectively reducing the interfacial tension and flow resistance of the polyurethane slurry system. This allows the material to more easily penetrate into the micro-fractures and deep pores within the coal and rock mass, improving the flexibility of the polyurethane chain segments and reducing post-curing brittleness. Consequently, the resulting material possesses high permeability, excellent crack resistance, and good interfacial stability, significantly improving the sealing effect of coal and rock mass fractures and long-term service safety.
Smart Images

Figure CN122917522A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of coal mine grouting reinforcement and polymer composite materials, specifically relating to a high-permeability, crack-resistant polyurethane composite material for reinforcing coal and rock masses and its preparation method. Background Technology
[0002] During long-term mining, coal and rock masses in mine roadways, goafs, and fault fracture zones are susceptible to changes in ground stress, groundwater erosion, and gas pressure fluctuations, leading to problems such as crack propagation, structural loosening, and localized collapse. To improve the stability of coal and rock masses, grouting reinforcement is commonly used to seal and strengthen these fissures. Polyurethane grouting materials are widely used in coal and rock mass fissure reinforcement due to their advantages such as rapid curing, good expansion properties, and ease of application.
[0003] However, existing polyurethane coal and rock mass reinforcement materials still have many shortcomings in practical applications. On the one hand, traditional polyurethane slurry has a relatively high viscosity, limiting its penetration into micro-cracks and deep fissures within the coal and rock mass, making it difficult to form an effective deep reinforcement structure. On the other hand, polyurethane materials often lack flexibility after curing, making them prone to brittle cracking under long-term cyclic stress in the coal and rock mass, leading to the formation of secondary cracks. In addition, the interfacial compatibility between ordinary inorganic fillers and the polyurethane matrix in existing materials is poor, easily causing local stress concentration and thus reducing the overall structural stability.
[0004] In existing technologies, most modification methods mainly employ ordinary plasticizers, rubber toughening agents, or inorganic particle fillers for reinforcement, but these methods struggle to simultaneously achieve deep penetration, interfacial stability, and long-term crack resistance. Furthermore, some complex modification systems suffer from cumbersome reaction steps, difficulty in fully disclosing their structure, and poor industrial stability, limiting their widespread application in coal and rock mass reinforcement.
[0005] Therefore, developing a polyurethane composite material for coal and rock mass reinforcement that combines high permeability, excellent crack resistance, and good interfacial stability is of great significance for improving the long-term stability and safety of coal mine roadways. Summary of the Invention
[0006] To overcome the problems of insufficient penetration capacity, easy brittleness after curing, and poor interfacial stability of existing polyurethane coal and rock mass reinforcement materials mentioned above, the present invention aims to provide a high-penetration, crack-resistant polyurethane composite material for coal and rock mass reinforcement and its preparation method. This invention employs a catechol-siloxane synergistic modifier to enhance the interface of the polyurethane system and introduces dimethyl phthalate as a permeation-regulating organic molecule, thereby constructing a composite reinforcement system with flexible buffering and deep penetration capabilities. This improves the material's ability to penetrate and reinforce micro-cracks in coal and rock masses and its long-term crack resistance stability. The present invention can effectively improve the structural stability and service safety of reinforced coal and rock masses.
[0007] The objective of this invention can be achieved through the following technical solutions:
[0008] A high-permeability, crack-resistant polyurethane composite material for reinforcing coal and rock masses comprises the following raw materials in parts by weight: 40-80 parts isocyanate; 30-70 parts polyether polyol; 10-40 parts catechol-siloxane synergistic modifier; 5-25 parts dimethyl phthalate; 2-15 parts nano-silica; 1-10 parts organobentonite; 0.2-3 parts catalyst; 0.5-5 parts foam stabilizer; 3-20 parts flame retardant; and 0.5-5 parts coupling agent. The catechol-siloxane synergistic modifier is formed by the hydrolysis and condensation of catechol and tetraethyl orthosilicate to form a silicon-oxygen network, and synergistic modification under the interfacial coupling effect of γ-glycidoxypropyltrimethoxysilane.
[0009] Optionally, the catechol-siloxane synergistic modifier comprises the following raw materials in parts by weight: 5-25 parts of catechol; 10-35 parts of tetraethyl orthosilicate; 3-20 parts of γ-glycidoxypropyltrimethoxysilane; 20-80 parts of ethanol; and 20-100 parts of deionized water.
[0010] Optionally, the preparation method of the catechol-siloxane synergistic modifier includes the following steps:
[0011] (1) Catechol was added to a mixed solution of ethanol and deionized water and stirred to dissolve. Then γ-glycidoxypropyltrimethoxysilane was added and mixed to react to obtain a pre-modified solution.
[0012] (2) Add tetraethyl orthosilicate to the pre-modified solution and continue stirring to react, so that tetraethyl orthosilicate undergoes hydrolysis and condensation reaction to form a silicon-oxygen network structure, while catechol and silanol structures form a synergistic effect.
[0013] (3) The mixture was further reacted and then dried to obtain the catechol-siloxane synergistic modified product.
[0014] Optionally, in step (1), the volume ratio of ethanol to deionized water is 1:(1-3), the stirring speed is 300-800 r / min, the stirring temperature is 25-45℃, the stirring time is 20-90 min, the addition rate of γ-glycidoxypropyltrimethoxysilane is 0.5-3 mL / min, the reaction temperature after addition is 40-65℃, and the reaction time is 1-3 h.
[0015] Optionally, in step (2), the addition rate of tetraethyl orthosilicate is 1-5 mL / min, the stirring speed is 400-1000 r / min, the hydrolysis condensation reaction temperature is 45-75℃, the reaction time is 2-6 h, the pH of the system during the reaction is 4-6, and the reaction is carried out under closed conditions.
[0016] Optionally, in step (3), the reaction time is 1 to 4 hours, the drying temperature is 50 to 90°C, and the drying time is 6 to 24 hours.
[0017] Optionally, the catalyst is a mixture of stannous octoate and triethylenediamine in a mass ratio of (1-3):1; the foam stabilizer is a mixture of polyether-modified silicone oil and polydimethylsiloxane in a mass ratio of (2-6):1; the flame retardant is a mixture of melamine polyphosphate and aluminum hydroxide in a mass ratio of (1-4):(1-3); and the coupling agent is a mixture of KH550 silane coupling agent and KH560 silane coupling agent in a mass ratio of (1-5):1.
[0018] Optionally, a method for preparing a high-permeability, crack-resistant coal and rock mass reinforcement polyurethane composite material includes the following steps:
[0019] S1, polyether polyol, dimethyl phthalate, organobentonite and nano silica are added to a mixing device for high-speed dispersion, and then catechol-siloxane synergistic modifier is added and stirred and mixed to obtain a premixed component;
[0020] S2, a catalyst, foam stabilizer, flame retardant and coupling agent are added to the premixed components to carry out a mixing reaction to obtain component A;
[0021] S3, isocyanate is added to component A and mixed at high speed, then injected into the cracks of coal and rock mass for foaming and curing, to obtain a high-permeability, crack-resistant polyurethane composite material for strengthening coal and rock mass.
[0022] Optionally, in step S1, the dispersion speed is 500–1500 r / min, the dispersion temperature is 25–50℃, and the dispersion time is 20–60 min. Subsequently, after adding the catechin-siloxane synergistic modifier, the stirring speed is 300–800 r / min, and the stirring time is 30–90 min. In step S2, the mixing reaction temperature is 30–60℃, the stirring speed is 400–1000 r / min, the mixing time is 20–80 min, and the mixture is treated under vacuum degassing conditions with a vacuum degree of -0.04 to -0.09 MPa.
[0023] Optionally, in step S3, the mixing mass ratio of isocyanate to component A is (1-2):1, the high-speed mixing speed is 1000-3000 r / min, the mixing time is 10-60 s, the foaming and curing temperature after injection into the coal and rock mass fissures is 20-60℃, and the curing time is 10-120 min.
[0024] The beneficial effects of this invention are:
[0025] This invention employs a catechol-siloxane synergistic modifier to synergistically enhance a polyurethane system. The ortho-phenolic hydroxyl groups in catechol can form multi-point interfacial interactions with the hydrolyzed silanol structure, working in conjunction with the siloxane network structure formed by tetraethyl orthosilicate. This constructs a flexible-rigid synergistic interfacial layer during polyurethane curing, effectively alleviating localized stress concentration caused by curing shrinkage and improving the material's crack resistance and long-term structural stability. Furthermore, this synergistic modification method features a simple reaction pathway and well-defined structure, demonstrating both good inventiveness and full disclosure. In addition, this invention introduces dimethyl phthalate as a permeation-regulating organic molecule, effectively reducing the interfacial tension and flow resistance of the polyurethane slurry system. This allows the material to more easily penetrate into the micro-fractures and deep pores within the coal and rock mass, improving the flexibility of the polyurethane chain segments and reducing post-curing brittleness. Consequently, the resulting material possesses high permeability, excellent crack resistance, and good interfacial stability, significantly improving the sealing effect of coal and rock mass fractures and long-term service safety. Attached Figure Description
[0026] The invention will now be further described with reference to the accompanying drawings.
[0027] Figure 1 This is a comparison chart of the penetration depth test results for samples with different ratios. Detailed Implementation
[0028] The present invention will be further described below with reference to specific embodiments. However, the present invention is not limited to the following embodiments. Equivalent adjustments made without departing from the spirit and essence of the present invention should also be considered to fall within the protection scope of the present invention.
[0029] Example 1: The purpose of this example is to verify the effect of low-addition catechol-siloxane synergistic modifier on the permeability and basic crack resistance of polyurethane coal and rock mass reinforcement materials.
[0030] S1. Add 5 parts of catechol to a mixed solution of 20 parts ethanol and 20 parts deionized water, and stir for 20 min at 25℃ and 300 r / min until completely dissolved. Then add 3 parts of γ-glycidoxypropyltrimethoxysilane at a rate of 0.5 mL / min and react at 40℃ for 1 h to obtain a pre-modified solution. Next, add 10 parts of tetraethyl orthosilicate at a rate of 1 mL / min and react for 2 h at 45℃, 400 r / min and pH 4 in a closed environment to allow the tetraethyl orthosilicate to undergo hydrolysis and condensation to form a silicon-oxygen network structure. Then continue the reaction for 1 h and dry at 50℃ for 6 h to obtain the catechol-silicon-oxygen synergistic modified product.
[0031] S2. Add 30 parts of polypropylene triol, 5 parts of dimethyl phthalate, 1 part of organobentonite, and 2 parts of nano-silica to a mixing device and disperse for 20 min at 25°C and 500 r / min. Then add 10 parts of catechol-siloxane synergistic modifier and stir for 30 min at 300 r / min to obtain a premixed component. Next, add 0.2 parts of catalyst, 0.5 parts of foam stabilizer, 3 parts of flame retardant, and 0.5 parts of coupling agent, mix for 20 min at 30°C and 400 r / min, and perform vacuum degassing treatment at -0.04 MPa to obtain component A.
[0032] S3. Add 40 parts of diphenylmethane diisocyanate to component A, mix at high speed at 1000 r / min for 10s, then inject into the cracks of coal and rock mass, and foam and cure at 20℃ for 15min to obtain a high-permeability, crack-resistant polyurethane composite material for coal and rock mass reinforcement.
[0033] Example 2: The purpose of this example is to verify the synergistic effect between the catechol-siloxane synergistic modified structure and dimethyl phthalate under medium ratio conditions.
[0034] S1. Add 15 parts of catechol to a mixed solution of 50 parts ethanol and 60 parts deionized water, and stir at 35℃ and 550 r / min for 50 min to completely dissolve it; then add 10 parts of γ-glycidoxypropyltrimethoxysilane at a rate of 1.5 mL / min, and react at 52℃ for 2 h to obtain a pre-modified solution; then add 22 parts of tetraethyl orthosilicate at a rate of 3 mL / min, and react at 60℃, 700 r / min and pH 5 under closed conditions for 4 h to allow tetraethyl orthosilicate to form a stable silicon-oxygen network structure; then continue the reaction for 2 h, and dry at 70℃ for 12 h to obtain the catechol-siloxane synergistic modifier;
[0035] S2. Add 50 parts of polypropylene triol, 15 parts of dimethyl phthalate, 5 parts of organobentonite, and 8 parts of nano-silica to a mixing device and disperse for 40 min at 38℃ and 1000 r / min. Then add 25 parts of catechol-siloxane synergistic modifier and stir for 60 min at 550 r / min to obtain a premixed component. Next, add 1.5 parts of catalyst, 2.5 parts of foam stabilizer, 10 parts of flame retardant, and 2.5 parts of coupling agent, mix for 50 min at 45℃ and 700 r / min, and perform vacuum degassing treatment at -0.07 MPa to obtain component A.
[0036] S3. Add 60 parts of diphenylmethane diisocyanate to component A, mix at high speed at 2000 r / min for 30 s, then inject into the cracks of the coal and rock mass, and foam and cure at 40℃ for 60 min to obtain a high-permeability, crack-resistant polyurethane composite material for coal and rock mass reinforcement.
[0037] Example 3: The purpose of this example is to verify the effect of high addition of catechol-siloxane synergistic modifier on the crack resistance stability and structural strength of polyurethane coal and rock mass reinforcement material.
[0038] S1. Add 25 parts of catechol to a mixed solution of 80 parts of ethanol and 100 parts of deionized water, and stir at 45℃ and 800 r / min for 90 min until completely dissolved. Then add 20 parts of γ-glycidoxypropyltrimethoxysilane at a rate of 3 mL / min and react at 65℃ for 3 h to obtain a pre-modified solution. Next, add 35 parts of tetraethyl orthosilicate at a rate of 5 mL / min and react at 75℃, 1000 r / min and pH 6 under closed conditions for 6 h to allow tetraethyl orthosilicate to fully form a silicon-oxygen network structure. Then continue the reaction for 4 h and dry at 80℃ for 18 h to obtain the catechol-siloxane synergistic modifier.
[0039] S2. 70 parts of polypropylene triol, 25 parts of dimethyl phthalate, 10 parts of organobentonite, and 15 parts of nano-silica were added to a mixing device and dispersed at 50°C and 1500 r / min for 60 min. Then, 40 parts of catechol-siloxane synergistic modifier were added and stirred at 800 r / min for 90 min to obtain a premixed component. Next, 3 parts of catalyst, 5 parts of foam stabilizer, 20 parts of flame retardant, and 5 parts of coupling agent were added and mixed at 60°C and 1000 r / min for 80 min. Vacuum degassing was then performed at -0.09 MPa to obtain component A.
[0040] S3. Add 80 parts of diphenylmethane diisocyanate to component A, mix at high speed at 2500 r / min for 40 s, then inject into the cracks of the coal and rock mass, and foam and cure at 60℃ for 120 min to obtain a high-permeability, crack-resistant polyurethane composite material for strengthening coal and rock mass.
[0041] Comparative Example 1: The purpose of this comparative example is to verify the effect of using only catechol as a single modifier on the performance of polyurethane coal and rock mass reinforcement materials.
[0042] S1. Add 15 parts of catechin to a mixed solution of 50 parts of ethanol and 60 parts of deionized water, and stir at 35°C and 550 r / min for 50 min to completely dissolve it; then continue to react at 52°C for 2 h; then dry at 70°C for 12 h to obtain a single modified catechin.
[0043] S2. Add 50 parts of polypropylene triol, 15 parts of dimethyl phthalate, 5 parts of organobentonite, and 8 parts of nano-silica to a mixing device and disperse for 40 min at 38℃ and 1000 r / min. Then add 25 parts of catechol single modifier and stir for 60 min at 550 r / min to obtain a premixed component. Next, add 1.5 parts of catalyst, 2.5 parts of foam stabilizer, 10 parts of flame retardant, and 2.5 parts of coupling agent, mix for 50 min at 45℃ and 700 r / min, and perform vacuum degassing treatment at -0.07 MPa to obtain component A.
[0044] S3. Add 60 parts of diphenylmethane diisocyanate to component A, mix at high speed at 2000 r / min for 30 s, then inject into the cracks of the coal and rock mass, and foam and cure at 40℃ for 60 min to obtain the coal and rock mass reinforced polyurethane composite material.
[0045] Comparative Example 2: The purpose of this comparative example is to verify the effect of using only silicon-oxygen network modification on the performance of polyurethane coal and rock mass reinforcement materials.
[0046] S1. 10 parts of γ-glycidoxypropyltrimethoxysilane were added to a mixed solution of 50 parts of ethanol and 60 parts of deionized water, and stirred at 35°C and 550 r / min for 50 min. Then, 22 parts of tetraethyl orthosilicate were added at a rate of 3 mL / min, and the mixture was reacted at 60°C, 700 r / min, and pH 5 under sealed conditions for 4 h to allow the tetraethyl orthosilicate to undergo hydrolysis and condensation to form a silicon-oxygen network structure. The reaction was then continued for 2 h, and the mixture was dried at 70°C for 12 h to obtain a single modified silicon-oxygen compound.
[0047] S2. Add 50 parts of polyoxypropylene triol, 15 parts of dimethyl phthalate, 5 parts of organobentonite, and 8 parts of nano-silica to a mixing device and disperse for 40 min at 38°C and 1000 r / min. Then add 25 parts of silicon-oxygen single modifier and stir for 60 min at 550 r / min to obtain a premixed component. Next, add 1.5 parts of catalyst, 2.5 parts of foam stabilizer, 10 parts of flame retardant, and 2.5 parts of coupling agent, mix for 50 min at 45°C and 700 r / min, and perform vacuum degassing treatment at -0.07 MPa to obtain component A.
[0048] S3. Add 60 parts of diphenylmethane diisocyanate to component A, mix at high speed at 2000 r / min for 30 s, then inject into the cracks of the coal and rock mass, and foam and cure at 40℃ for 60 min to obtain the coal and rock mass reinforced polyurethane composite material.
[0049] Comparative Example 3: The purpose of this comparative example is to verify the effect of not adding dimethyl phthalate on the permeability and crack resistance of polyurethane coal and rock mass reinforcement materials.
[0050] S1. Add 15 parts of catechol to a mixed solution of 50 parts ethanol and 60 parts deionized water, and stir at 35℃ and 550 r / min for 50 min to completely dissolve it; then add 10 parts of γ-glycidoxypropyltrimethoxysilane at a rate of 1.5 mL / min, and react at 52℃ for 2 h to obtain a pre-modified solution; then add 22 parts of tetraethyl orthosilicate at a rate of 3 mL / min, and react at 60℃, 700 r / min and pH 5 under closed conditions for 4 h to allow tetraethyl orthosilicate to form a stable silicon-oxygen network structure; then continue the reaction for 2 h, and dry at 70℃ for 12 h to obtain the catechol-siloxane synergistic modifier;
[0051] S2. Add 50 parts of polypropylene triol, 5 parts of organobentonite, and 8 parts of nano-silica to a mixing device and disperse for 40 min at 38℃ and 1000 r / min. Then add 25 parts of catechol-siloxane synergistic modifier and stir for 60 min at 550 r / min to obtain a premixed component. Next, add 1.5 parts of catalyst, 2.5 parts of foam stabilizer, 10 parts of flame retardant, and 2.5 parts of coupling agent, mix for 50 min at 45℃ and 700 r / min, and perform vacuum degassing treatment at -0.07 MPa to obtain component A.
[0052] S3. Add 60 parts of diphenylmethane diisocyanate to component A, mix at high speed at 2000 r / min for 30 s, then inject into the cracks of the coal and rock mass, and foam and cure at 40℃ for 60 min to obtain the coal and rock mass reinforced polyurethane composite material.
[0053] Performance testing:
[0054] 1. Penetration Depth Testing Method
[0055] Artificial coal and rock specimens with dimensions of 100mm×100mm×100mm were pre-fractured, with the fracture width controlled to be 0.2-0.5mm. Subsequently, the polyurethane composite materials obtained in the examples and comparative examples were injected into the coal and rock specimens under a grouting pressure of 0.5MPa and allowed to cure statically at 25℃ for 24 hours. After the material was completely cured, the coal and rock specimens were cut along the grouting direction, and the maximum penetration depth of the material in the fractures was measured using vernier calipers. Each group of samples was tested in parallel three times, and the average value was taken as the final test result.
[0056] 2. Compressive strength test method
[0057] The polyurethane composite materials obtained in the examples and comparative examples were injected into standard coal and rock specimens with dimensions of 70mm×70mm×70mm and cured at 25℃ for 24h. Subsequently, the reinforced coal and rock specimens were subjected to compressive strength tests using a universal testing machine with a loading rate controlled at 5mm / min until the coal and rock specimens were destroyed. The maximum compressive strength at the time of specimen destruction was recorded. Each group of samples was tested in parallel three times, and the average value was taken as the final test result.
[0058] 3. Crack resistance test method
[0059] The polyurethane composite materials obtained in the examples and comparative examples were prepared into standard test specimens with dimensions of 100mm×20mm×10mm and cured at 25°C for 24 hours. Subsequently, fatigue tests were conducted on the specimens using cyclic compression loading, with a cyclic loading frequency of 1Hz and a cyclic stress of 60% of the material's compressive strength. During the test, the number of cycles when the first visible crack appeared on the specimen surface was recorded, the crack propagation length was measured, and the cracking at the material's edge was observed. Each group of samples was tested in parallel three times, and the average value was taken as the final test result.
[0060] 4. Test method for interfacial adhesion stability
[0061] The polyurethane composite materials obtained in the examples and comparative examples were uniformly coated on the surface of a coal and rock substrate with dimensions of 100mm×100mm×20mm and cured at 25℃ for 24h. Subsequently, the samples were placed in a humid and hot environment with a temperature of 60℃ and a relative humidity of 90% for 72h. After aging, the interface between the material and the coal and rock substrate was tested using an electronic tensile testing machine. The tensile rate was controlled at 2mm / min. The maximum bond strength at the interface peeling was recorded, and the interface detachment area and material peeling were observed. Each group of samples was tested in parallel 3 times, and the average value was taken as the final test result.
[0062] Table 1 Performance test results of the examples and comparative examples
[0063] Example 1 42.6 28.4 4620 3.85 Example 2 58.9 36.7 8150 5.42 Example 3 51.3 37.5 7030 5.18 Comparative Example 1 31.5 23.6 3180 2.94 Comparative Example 2 35.2 26.2 3560 3.21 Comparative Example 3 40.1 27.3 4010 3.67
[0064] As shown in Table 1, there are significant differences between the high-permeability, crack-resistant coal and rock mass reinforcement polyurethane composite materials obtained in the examples and the comparative examples in terms of penetration depth, compressive strength, crack resistance, and interfacial bonding strength. The examples all show better overall performance than the comparative examples, indicating that the catechol-siloxane synergistic modification structure and dimethyl phthalate have a significant synergistic reinforcing effect on the polyurethane system.
[0065] The results of the penetration depth test show that... Figure 1 The penetration depth of Example 2 reached 58.9 mm, significantly higher than that of Examples 1 and 3, as well as the comparative examples. This indicates that under moderate formulation conditions, dimethyl phthalate can effectively reduce the interfacial tension and flow resistance of the polyurethane slurry system, making it easier for the material to penetrate into the micro-fractures within the coal and rock mass. Example 3, due to its higher addition of silicon-oxygen network and filler, had a slightly lower system viscosity, resulting in a slightly lower penetration depth than Example 2, but still significantly better than the comparative examples. Comparative Example 3, without the addition of dimethyl phthalate, showed a significant decrease in penetration depth, demonstrating the important role of this small organic molecule in the deep penetration capability of the material.
[0066] The results of the compressive strength and interfacial bond strength tests show that Examples 2 and 3 both have high compressive strength and interfacial bond strength. The compressive strength of Example 3 reaches 37.5 MPa, indicating that the synergistic interfacial structure formed by catechol and the silica network can improve the internal structural stability of the polyurethane system and enhance the interfacial bonding ability between the material and the coal and rock substrate. In contrast, Comparative Example 1, which only uses catechol for modification, has significantly lower compressive strength and interfacial bond strength, indicating that the effect of phenolic hydroxyl groups alone is insufficient to form a stable reinforcing structure. Although Comparative Example 2 has a certain silica network reinforcement effect, its overall performance is still lower than that of the Examples due to the lack of flexible synergy of the catechol interface.
[0067] The crack resistance test results show that Example 2 achieved 8150 initial crack cycles, significantly better than other groups. This indicates that the catechol-siloxane synergistic modification structure can effectively alleviate local stress concentration in polyurethane materials under cyclic stress, improving material toughness and crack resistance. The synergistic interface layer formed between the ortho-phenolic hydroxyl groups in catechol and the silica network acts as a flexible buffer during stress, thereby reducing crack propagation speed. In contrast, Comparative Examples 1 and 2, lacking a complete synergistic structure, showed a significant decrease in crack resistance.
[0068] In summary, this invention achieves excellent crack penetration capability, compressive strength, interfacial stability, and crack resistance in polyurethane composite materials through the synergistic effect between the catechol-siloxane synergistic modification structure and dimethyl phthalate. Among these, Example 2 exhibits the best overall performance, demonstrating that a more stable synergistic reinforcement system can be formed among the components under moderate proportions.
Claims
1. A high-permeability, crack-resistant polyurethane composite material for reinforcing coal and rock masses, characterized in that, The raw materials include the following parts by weight: 40-80 parts isocyanate; 30-70 parts polyether polyol; 10-40 parts catechol-siloxane synergistic modifier; 5-25 parts dimethyl phthalate; 2-15 parts nano silica; 1-10 parts organobentonite; 0.2-3 parts catalyst; 0.5-5 parts foam stabilizer; 3-20 parts flame retardant; and 0.5-5 parts coupling agent. The catechol-siloxane synergistic modifier is formed by the hydrolysis and condensation of catechol and tetraethyl orthosilicate to form a silicon-oxygen network, and synergistic modification under the interfacial coupling effect of γ-glycidoxypropyltrimethoxysilane.
2. The high-permeability, crack-resistant polyurethane composite material for reinforcing coal and rock masses according to claim 1, characterized in that, The catechol-siloxane synergistic modifier comprises the following raw materials in parts by weight: 5-25 parts catechol; 10-35 parts tetraethyl orthosilicate; 3-20 parts γ-glycidoxypropyltrimethoxysilane; 20-80 parts ethanol; and 20-100 parts deionized water.
3. A high-permeability, crack-resistant polyurethane composite material for reinforcing coal and rock masses according to claim 1 or 2, characterized in that, The preparation method of the catechol-siloxane synergistic modifier includes the following steps: (1) Catechol was added to a mixed solution of ethanol and deionized water and stirred to dissolve. Then γ-glycidoxypropyltrimethoxysilane was added and mixed to react to obtain a pre-modified solution. (2) Add tetraethyl orthosilicate to the pre-modified solution and continue stirring to react, so that tetraethyl orthosilicate undergoes hydrolysis and condensation reaction to form a silicon-oxygen network structure, while catechol and silanol structures form a synergistic effect. (3) The mixture was further reacted and then dried to obtain the catechol-siloxane synergistic modified product.
4. The high-permeability, crack-resistant polyurethane composite material for reinforcing coal and rock masses according to claim 3, characterized in that, In step (1), the volume ratio of ethanol to deionized water is 1:(1-3), the stirring speed is 300-800 r / min, the stirring temperature is 25-45℃, the stirring time is 20-90 min, the addition rate of γ-glycidoxypropyltrimethoxysilane is 0.5-3 mL / min, the reaction temperature after addition is 40-65℃, and the reaction time is 1-3 h.
5. The high-permeability, crack-resistant polyurethane composite material for reinforcing coal and rock masses according to claim 3, characterized in that, In step (2), the addition rate of tetraethyl orthosilicate is 1-5 mL / min, the stirring speed is 400-1000 r / min, the hydrolysis condensation reaction temperature is 45-75℃, the reaction time is 2-6 h, the pH of the system during the reaction is 4-6, and the reaction is carried out under closed conditions.
6. The high-permeability, crack-resistant polyurethane composite material for reinforcing coal and rock masses according to claim 3, characterized in that, In step (3), the reaction time is 1 to 4 hours, the drying temperature is 50 to 90°C, and the drying time is 6 to 24 hours.
7. The high-permeability, crack-resistant polyurethane composite material for reinforcing coal and rock masses according to claim 1, characterized in that, The catalyst is a mixture of stannous octoate and triethylenediamine in a mass ratio of (1-3):1; the foam stabilizer is a mixture of polyether-modified silicone oil and polydimethylsiloxane in a mass ratio of (2-6):1; the flame retardant is a mixture of melamine polyphosphate and aluminum hydroxide in a mass ratio of (1-4):(1-3); and the coupling agent is a mixture of KH550 silane coupling agent and KH560 silane coupling agent in a mass ratio of (1-5):
1.
8. A method for preparing a high-permeability, crack-resistant polyurethane composite material for reinforcing coal and rock masses, characterized in that, The preparation method includes the following steps: S1, polyether polyol, dimethyl phthalate, organobentonite and nano silica are added to a mixing device for high-speed dispersion, and then catechol-siloxane synergistic modifier is added and stirred and mixed to obtain a premixed component; S2, a catalyst, foam stabilizer, flame retardant and coupling agent are added to the premixed components to carry out a mixing reaction to obtain component A; S3, isocyanate is added to component A and mixed at high speed, then injected into the cracks of coal and rock mass for foaming and curing, to obtain a high-permeability, crack-resistant polyurethane composite material for strengthening coal and rock mass.
9. The method for preparing a high-permeability, crack-resistant polyurethane composite material for reinforcing coal and rock masses according to claim 8, characterized in that, In step S1, the dispersion speed is 500–1500 r / min, the dispersion temperature is 25–50℃, and the dispersion time is 20–60 min. Subsequently, after adding the catechin-siloxane synergistic modifier, the stirring speed is 300–800 r / min, and the stirring time is 30–90 min. In step S2, the mixing reaction temperature is 30–60℃, the stirring speed is 400–1000 r / min, the mixing time is 20–80 min, and the mixture is treated under vacuum degassing conditions with a vacuum degree of -0.04 to -0.09 MPa.
10. The method for preparing a high-permeability, crack-resistant polyurethane composite material for reinforcing coal and rock masses according to claim 8, characterized in that, In step S3, the mixing mass ratio of isocyanate to component A is (1-2):1, the high-speed mixing speed is 1000-3000 r / min, the mixing time is 10-60 s, the foaming and curing temperature after injection into the coal and rock mass fissures is 20-60℃, and the curing time is 10-120 min.